9 Assessment of performance tested bull characteristics and their effect on price. (1st March 2018) - Thinguldstad, B M; Russell, L; Tucker, J J; Buono, G A; Segers, J R
Abstract: Performance tested bulls are a valuable commodity for Southeastern cattle producers. Consignors and bull evaluation centers are constantly interested in knowing which factors impact a bull's ability to excel in a performance test, and ultimately increase sale price. Performance of yearling bulls can be affected by a variety of factors including inherited genetic potential and physical strain such as illness and stress. Illness is common in bull evaluation centers where animals are congregated in a new environment and exposed to pen-mates from different farms and backgrounds. Illness requires bulls to be treated, and will impact performance characteristics, and may potentially affect a bull's value or sale eligibility. Therefore, the objective of this analysis was to assess the impact of treatment frequency, as well as average daily gain (ADG), weight per day of age (WDA), BW, and breed on price and sale eligibility on 619 bulls in the Tifton Bull Evaluation Sale from 2012–2016. A Tobit model was used to account for bull sale eligibility in the price analysis. Price coefficients were generated and serve as indicators of factors affecting price in the Tifton Bull Sale on a per head basis. Compared to year 4 (2015–2016), average price in year 1 (2012–2013) was 295.43 lower ( P= 0.003; SEM=98.21). Both year 2 (2013–2014) and year 3 (2014–2015) had higher ( P< 0.001; SEM=106.57) prices compared to year 4 at 644.52 and 1060.51, respectively. Treatment frequency did not affect ( P= 0.18; SEM=49.37) price; however, there was numerical decease in price of 66.00 each time a bull was treated. For every kg of weight increase, price increased ( P< 0.001; SEM = 0.90) 3.93. Sale price increased ( P <0.001; SEM=216.12) 1, 256.13, for every 1-kg increase in ADG. For every 1-kg increase in WDA, price increased ( P< 0.001; SEM=435.29) 2, 398.98. Charolais (n=24), Simmental (n=77) and Hereford (n=35) bulls achieved sale prices similar ( P≥ 0.13; SEM=186.85) to Angus bulls (n=310); however, both SimAngus (n=128) and all other breeds (n=45) decreased ( P≤ 0.01; SEM=150.92) price on average by 252.19 and 374.41, respectively, compared to Angus. These data indicate that ADG, WDA, weight and breed type have a profound impact on sale price in performance tested bulls. Treatment frequency was not an adequate predictor of price; therefore, incidence of morbidity did not affect bull sale eligibility.